2005
DOI: 10.1017/s1355617705050356
|View full text |Cite
|
Sign up to set email alerts
|

Semantic and phonemic sequence effects in random word generation: A dissociation between Alzheimer's and Huntington's disease patients

Abstract: Alzheimer's disease (AD) patients perform worse on category than letter fluency tasks, while Huntington's disease (HD) patients show the reverse pattern or comparable impairment on both tasks. We developed a random word generation task to further investigate these deficits. Twenty AD and 16 HD patients and 20 elderly and 16 middle-aged controls guessed which of three pictures (hat, cat, or dog) landed on a die's top face sixty times. Three consecutive response pairings were possible: semantic (cat-dog), phonem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…In previous studies, patients with Alzheimer's disease have shown more difficulty with semantic verbal fluency than with phonemic verbal fluency, and the impairment has been attributed to a breakdown in the semantic knowledge concerning word categorization, which depends on the integrity of the temporal ventral area and fusiform gyrus. 13,14 Such reports support the hypothesis that the more frequently impaired semantic verbal fluency, as compared with phonemic verbal fluency, of our patients is likely associated with an injury in the territory of the PCA. However, decline of performance on the phonological fluency task, a skill reliant on frontal lobe function, was also demonstrated in patients with occipital lobe lesions extending to the splenium or to the posterior ventral temporal lobe.…”
Section: Discussionsupporting
confidence: 86%
“…In previous studies, patients with Alzheimer's disease have shown more difficulty with semantic verbal fluency than with phonemic verbal fluency, and the impairment has been attributed to a breakdown in the semantic knowledge concerning word categorization, which depends on the integrity of the temporal ventral area and fusiform gyrus. 13,14 Such reports support the hypothesis that the more frequently impaired semantic verbal fluency, as compared with phonemic verbal fluency, of our patients is likely associated with an injury in the territory of the PCA. However, decline of performance on the phonological fluency task, a skill reliant on frontal lobe function, was also demonstrated in patients with occipital lobe lesions extending to the splenium or to the posterior ventral temporal lobe.…”
Section: Discussionsupporting
confidence: 86%
“…Although action and letter fluency greatly rely on integrity of executive functions, animal fluency requires both executive functions and semantic knowledge integrity. Low performance in letter and semantic fluency tasks in HD was reported by Henry et al 3 in a meta-analytic study, and a dissociation between semantic and letter fluency (with a poorer performance in letter fluency) has also been described 21 . Time restriction to perform the task may also be a factor that contributes to poor results 22 .…”
Section: Discussionmentioning
confidence: 74%
“…They are characterized as executive in nature; rely on higher order cognitive processes such as initiation, conceptual reasoning, self-monitoring, and cognitive flexibility; have been linked to frontal lobe functioning; and are known to be impaired in AD (Henry & Crawford, 2004;Lezak et al, 2004;March & Pattison, 2006). We also note that impairment on measures of semantic fluency, relative to phonemic fluency, is a hallmark of AD (Murphy et al, 2006;Taylor et al, 2005). Therefore, it is likely that the emergence of Semantic Fluency as the key predictor of reasoning in mild AD also reflects the impact of degradation in semantic networks on reasoning abilities regarding medical information.…”
Section: Discussionmentioning
confidence: 80%